An Automatic Interpretation method with Manufacturing Constraints on Topology Optimization and 3D Printing - Κανελλόπουλος, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2017)
The scope of this master thesis is to apply manufacturing constraints to a structural topology optimization problem. Then the produced shape automatically is interpreted in a CAD program so as to finally create 3D printing models. In the first chapter a brief historical report is presented while some papers which deal with topology optimization and architecture are reviewed. The second chapter includes the mathematical formulation of the topology optimization problem. The mathematical procedures that have been analyzed, focus on the typical SIMP compliance minimization. The third chapter begins with a short survey on matlab codes in literature that tackle the optimization problem. The main program is presented and all the new variables and functions are described. Three alternative scenarios are investigated: (a) default case, (b) non optimized areas and (c) beam elements. Several examples, illustrate the influence of each case in our final structures. In the fourth chapter the fully automatic interpretation is demonstrated. Image processing techniques is used to extract the boundaries of the optimized design. Afterwards the nodes are interpolated by NURBS and finally with the use of IGES the structure is imported in Solidworks. The procedure is described step by step and the code is explained thoroughly.In the final chapter a validation through the CAE software Ansys Workbench is performed in order to examine the mechanical behavior of the selected cases. An example of a possible application of the wrench problem is presented and also the embodiment of some cases into 3D printed items.